The Micro-Slip Damper Stiffness Effect on the Steady-State Characteristics of Turbine Blade - Tolephih, Moneer Hameed (Nahrain University College of Engineering Journal, 2007)
In this paper, a comprehensive study of friction damper stiffness effects on the response characteristics of a typical turbine blade executing steady-state motion, s explored. The damper is modeled as a one-bar microslip type assembled in the intermediate platform attachment of the blade leaving the other attachment of a shroud mass at the blade tip to be free. A discrete lumped mass approach, previously theorized in another paper, is employed to predict the response amplitudes as well as the slip length parameter at any state of the forced frequency including the resonance condition. The analysis covers a practical range of damper stiffness values adapted from relevant studies in this field. The present main outputs show that a magnificent rising of the response occurs with the increase in the stiffness, the characteristic behavior varies appreciably and the resonant amplitudes tend to increase linearly at high levels of damper stiffness, whereas the corresponding frequency and slip length show almost uniform trend. The results can serve very well for design and control purposes in the pre-manufacture stages of the given blade-damper system